’Tú’ genérico en el español de la Ciudad de México - Orozco, Leonor (Borealis – An International Journal of Hispanic Linguistics, 2019)
The purpose of this paper is to describe the use of generic you in the Spanish of Mexico City. A sociolinguistic study of the distribution of this pronominal subject is carried out. For this purpose, speech samples from two moments are analyzed, the first around 1970 and the second circa 2000. The results suggest that, on the one hand, generic you is used more and more frequently in Mexican Spanish and that there are more speakers who resort to their employment. On the other hand, the contexts of use of generic you have also been extended, because, although it occurs mainly with verbs in the present, it is also documented, to a lesser extent, in other contexts even with verbs in perfective aspect.